Neurodevelopmental Disorders in the International Classification of Diseases, 11th edition (ICD - 11): An overveiw - Stevanović, Dejan (Engrami, 2021)
Neurodevelopmental disorders include a wide range of disorders and impairments in the development of cognitive or motor functions. The eleventh revision of the International Classification of Diseases (ICD-11), which came out in 2018, and whose application should start in 2022, introduced for the first time the diagnostic group of neurodevelopmental disorders, which consists of disorders of intellectual development, developmental speech or language disorders, autism spectrum disorder (ASD), developmental learning disorder, developmental motor coordination disorder, attention deficit hyperactivity disorder (ADHD), stereotyped movement disorder, tic disoders and other specified neurodevelopmental disrders, as a residual category.  The aim of this brief overview was to present the main diagnostic categories in  the ICD - 11 that make up the group of neurodevelopmental disorders and to show the main changes in diagnosis using individual disorders using the ICD - 11 compared to the previous ICD - 10. It is believed that ICD - 11 will provide better conceptualization and understanding of psychopathology, including neurodevelopmental disabilities, among clinicians, and that in the coming decades, diagnosing the disorder will not only be easier, but also improved.
Keywords: difficulties; disabilities; development; children; diagnosis